Analysis of Proposed Adaptation of Fostered Environment and Evaluation of Built Environment in Bali in Facing Covid-19 - I Nyoman Gede Maha Putra (Architectural Research Journal, 2021)
At the time this paper started being written, the spread of the COVID-19 pandemic had been taking place for more than a year. To date, it has caused fear in society because the number of deaths it causes is nearly 3 million people, the effectiveness of the vaccines being developed is uncertain and there is no convincing drug available. As a result, the virus having hit almost all countries and regions around the world has affected the way humans behave and will have an impact on the architectural design and urban spaces in which humans live. This paper explores the possible criteria for architectural design and urban design in response to a pandemic, particularly in Bali. Plural society serves as the characteristic of the island whose inhabitants have traditional activities mixed with modern trends. The mixed society has a rich tradition of communal living with social activities involving large masses of people. To produce post pandemic design criteria, this study critically reviewed recent publications including peer-reviewed articles, journals, and expert’s blog posts. In the next stage, the results of the review were used to evaluate activity patterns and fostered environment at several locations in Bali. The locations observed included traditional houses in Ubud, urban houses in Denpasar, offices, and traditional markets. Secondary data were organised into several themes. Meanwhile, field observations were focused on the possibility of implementing Health protocols in different places as well as community compliance in complying with them. This study found that during the period of limiting community activities due to the pandemic, health, safety and environmental hygiene had received the attention of all groups. The study also revealed that the built environment tried to make many adjustments. Nevertheless, the effectiveness of these adjustments is questionable. For this reason, further research that will produce new built spaces needs to be carried out. It will result in the need for more detailed design criteria as a mechanism to prevent the spread of the virus.